The lateral buckling of steel I-shape beams with continuous torsional elastic restraints - Roman Bijak (Budownictwo i Architektura, 2013)
A simple model of the lateral buckling of steel I-shape beams with elastic and continuous torsional restraints was developed. The lateral buckling beams with free warping were formulated as differential equations in terms of torsion angle. The stability equations were approximately solved with the use of the Bubnow-Galerkin orthogonalization method. The proposed approximate formulas provide the estimation of lateral buckling moment with good enough accuracy for designing purposes.